Tuning riboflavin derivatives for photodynamic inactivation of pathogens - Leander B. Crocker; Ju Hyun Lee; Suraj Mital; Gabrielle C. Mills; Sina Schack; Andrea Bistrović-Popov; Christoph O. Franck; Ioanna Mela; Clemens F. Kaminski; Graham Christie; Ljiljana Fruk (Scientific Reports, 2022)
Abstract The development of effective pathogen reduction strategies is required due to the rise in antibiotic-resistant bacteria and zoonotic viral pandemics. Photodynamic inactivation (PDI) of bacteria and viruses is a potent reduction strategy that bypasses typical resistance mechanisms. Naturally occurring riboflavin has been widely used in PDI applications due to efficient light-induced reactive oxygen species (ROS) release. By rational design of its core structure to alter (photo)physical properties, we obtained derivatives capable of outperforming riboflavin’s visible light-induced PDI against E. coli and a SARS-CoV-2 surrogate, revealing functional group dependency for each pathogen. Bacterial PDI was influenced mainly by guanidino substitution, whereas viral PDI increased through bromination of the flavin. These observations were related to enhanced uptake and ROS-specific nucleic acid cleavage mechanisms. Trends in the derivatives’ toxicity towards human fibroblast cells were also investigated to assess viable therapeutic derivatives and help guide further design of PDI agents to combat pathogenic organisms.